Effects of managerial capabilities on performance audit and satisfaction of users of educational material at UGEL Puno, 2022 - Jamachi Arpasi, Norma Soledad (2024)
Objective. "To determine the effect of managerial and operational capabilities on the degree of compliance with the performance audit and user satisfaction in the distribution of educational material at UGEL Puno, 2022." Method. Non-experimental, cross-sectional, causal explanatory design, instruments: evaluation of 84 purchase files, interviews with 15 officials and a survey of a sample of 220 EBR directors from the UGEL-Puno area. SEM-PLS test. Results: The performance audit is 71.50% deficient and has a direct relationship with managerial capabilities, with β = 0.869, SD = 0.019; t = 45.366; and p = 0.000 < 0.05, explaining the relationship of 75.50%. Managerial capabilities are 69.70% deficient and have a direct relationship with user satisfaction with β = 0.310; DS= 0.104; t = 2.996; and p = 0.003 < 0.05, is significant, explaining the relationship of 9.60% which is very low and the users 71.90% are dissatisfied. Conclusion, the indirect effect of staff capabilities on the relationship of performance audit (X) and user satisfaction (X) is very strong for (X) and very weak for (Y) and explains the variance of the construct (X, Y).